Mehrsprachiges online-Wörterbuch zum Fachwortschatz der Verwaltungssprache des griechisch-römisch-byzantinischen Ägypten: das neue Fachwörterbuch (nFWB) - Reinhold Scholl; Christoph Weilbach (Digital Classics Online)
The „multilingual online dictionary of the technical administrative language of Greek, Roman and Byzantine Egypt“ (in short „neues Fachwörterbuch“) replaces, updates and extends its known predecessor, Friedrich Preisigke`s „Fachwörter des öffentlichen Verwaltungsdienstes Ägyptens: in den griechischen Papyrusurkunden der ptolemäisch-römischen Zeit“ which was published more than 100 years ago, in 1915. It offers not only a display of the lemmata with spelling variants and translations into the present academic languages German, English, French, Italian and Spanish, but also, among other features, a full-text search and the possibility to arrange the lemmata individually according to their respective subjects as well as sorting the search results according to different aspects. The „neues Fachwörterbuch“ indicates and links to their full-texts at www.papyri.info which represent the earliest and the latest record of a word‘s meaning; apart from that it provides bibliographical references and offers further information and links concerning the word and its meaning(s). In this paper we want to introduce the new Fachwörterbuch and explain the main features of the website.